Detection and recognition of objects on images based on MKV-classifiers - Murygin, K.V. (Искусственный интеллект, 2013)
In article the algorithm of combination of the binary properties widely used in practice at system engineering of the
automatic analysis of the visual information, in the form of the MKV-classifier is offered. Problems of training and using
of MKV- classifiers for the decision of detection problems and recognition of objects are considered. The offered
algorithms of training allow to generate more effective recognizing rules in comparison with known algorithm
AdaBoost, in particular it is essential to reduce number of used properties at identical classifying ability, at the expense
of more exact description of position of objects in feature space. Possibility of representation of the MKV- classifier in
the form of a decisions tree allows increasing essentially of computing efficiency of classification process. У статті пропонується алгоритм об’єднання бінарних властивостей, широко використовуваних на практиці
при розробці систем автоматичного аналізу візуальної інформації, у вигляді МКВ-класифікатора.
Розглядаються питання навчання й використання МКВ-класифікаторів для вирішення завдань виявлення
й розпізнавання об’єктів. Запропоновані алгоритми навчання дозволяють генерувати більш ефективні
вирішуючи правила в порівнянні з відомим алгоритмом AdaBoost, зокрема істотно скоротити число
використовуваних властивостей при однаковій якості класифікації за рахунок більш точного опису
положення об’єктів у просторі ознак. Можливість представлення МКВ-класифікатора у вигляді дерева
рішень дозволяє істотно збільшити обчислювальну ефективність процесу класифікації. В статье предлагается алгоритм объединения бинарных свойств, широко используемых на практике при
разработке систем автоматического анализа визуальной информации, в виде МКВ-классификатора.
Рассматриваются вопросы обучения и использования МКВ-классификаторов для решения задач
обнаружения и распознавания объектов. Предложенные алгоритмы обучения позволяют генерировать
более эффективные решающие правила по сравнению с известным алгоритмом AdaBoost, в частности
существенно сократить число используемых свойств при одинаковой классифицирующей способности, за
счет более точного описания положения объектов в пространстве признаков. Возможность представления
МКВ-классификатора в виде дерева решений позволяет существенно увеличить вычислительную
эффективность процесса классификации.